Caecal duplication, a case report - Michele Corroppolo; Elisa Pani; Maria Teresa Bortolami; Hamid Reza Sadri; Fabio Beretta; Clara Revetria; Giosuè Mazzero; Enrico Ciardini (PAGEPress Publications, 2021)
The caecum is one of the rarest sites of intestinal duplication cysts. The most common symptomatology includes vomiting, abdominal pain, abdominal distention, palpable mass and rectal bleeding. Most of the duplications are diagnosed within the first two years of life, including prenatal diagnosis. Only few cases of caecal duplication have been reported in the literature up to the present day. We are going to present a case of a five-years old girl with caecum duplication who reached our ward due to abdominal distension with no other symptoms.